Enhancing the participation of young minoritised fathers in peer research: An intersectional reflexive analysis of methods and ethics - Laura Way; Anna Tarrant; Linzi Ladlow (Methodological Innovations)
This article presents an intersectional, reflexive analysis of the research process, methods and ethical considerations involved in a community-based participatory study aimed at increasing and improving the participation of young and minoritised fathers, both in support settings and in research. Conducted by a peer research team comprising beneficiaries and a young male employee of a specialist support charity for young fathers, the substantive aim of Diverse Dads was to explore and address the limited diversity and inclusion of minoritised young fathers in contexts of family and multi-agency service provision. This aim prompted critical attention to questions of inclusion and empowerment for young fathers throughout the research process, including those from ethnic minority communities, as overlooked and under-represented populations in service contexts and research. Synthesising intersectionality and participation theories, we employ an ‘intersectional participatory framework’, to outline and interrogate four ‘critical moments’, and associated methodological strategies, that researchers might encounter in co-produced research with participants who are marginalised and/or minoritised. These are: (1) creating spaces to facilitate and enhance research participation, (2) fostering community empowerment through participation, (3) foregrounding minoritised voices and (4) (en)countering essentialism. Via these themes, we consider the possibilities for enhancing the inclusion and participation of marginalised and minoritised participants and explore the challenges and tradeoffs in research and practice contexts where engagement with such populations has proven challenging to overcome.